Chemical Properties of Acid Sulfate Soils Across Sulfuric Horizon Depths and Their Effects on Oil Palm Root Development - Hari Gunawan; Ingrid Ovie Yosephine; Muhammad Rizky Andrian (Jurnal Riset Perkebunan, 2026)
A problem encountered in oil palm cultivation on tidal acid sulfate soils is the pyrite content. If pyrite in the soil oxidizes, it will increase soil acidity and metal content, thereby impacting oil palm root growth. This study aims to analyze the chemical properties of acid sulfate soils at various depths within the sulfuric horizon and their impact on oil palm root development at PT. Sumber Asih Kebun Paya Rambe II, Aceh Tamiang. The study used a soil survey method with an exploratory-descriptive approach, including soil profile identification and the collection of 32 composite soil samples at four depths (0–20, 20–40, 40–60, 60–80 cm) in two blocks with different sulfuric horizon depths. pH analysis was performed using a pH meter in a soil-water suspension (1:2.5), while AI and Fe contents were determined using Atomic Absorption Spectrophotometry (AAS) after wet digestion. To evaluate root development, 8 root samples were taken purposively and analyzed using the oven-dry weight method (105°C). The results showed the lowest pH at 60–80 cm, namely 4.5 (Block 27) and 5.0 (Block 24). The highest AI content was also found in the same layer, namely 5.2572% and 3.7582%, while the highest Fe content was at a depth of 0–20 cm, respectively, 3.1274% and 2.8684%. Root development decreased significantly in locations with shallow sulfuric horizons, indicated by a decrease in root dry weight of 34–38% compared to locations with deeper sulfuric horizons. This study confirms that the position of the sulfuric horizon directly affects soil acidity, AI mobilization, and reduced oil palm root growth in acid sulfate soils.